Síntese de Penta-2,4-dienonitrilas e 2-Cianometileno-but-3-enoatos de Etila via Olefinação de Horner-Wadsworth-Emmons e sua Aplicação na Obtenção de 4-Trifluormetil-piridin-2(1H)-iminas Substituídas e 2H-Piran-2-onas Análogas . - Bencke, Carlos Eduardo (2013)
This paper presents the Horner-Wadsworth-Emmons olefination applied to preparing 22 new 5-alkoxy-3-trifluoromethyl-penta-2,4-dienenitriles (5), 5- phenylthio-3-trifluoromethyl-penta-2,4-dienenitriles (6) and ethyl 4-alkoxy-2- cyanomethylene-but-3-enoates (7) from the condensation between diethyl cyanomethylphosphonate (4) and β-alkoxyvinyl ketones (1), β-phenyltiovinyl ketones (2) and ethyl 4-alkoxy-2-oxo-but-3-enoates (3), furnishing the desired products with 10 to 93% yields. In a second step, this paper presents a simple and accessible novel synthetic route, for the preparation of a series of 30 unpublished 1,6- disubstituted 4-trifluoromethyl-pyridin-2(1H)-imines (14-19) from the condensation reaction of 5-aryl-3-trifluoromethyl-5-methoxy-penta-2,4- dienenitriles (Ar = Ph, 4-F-C6H4, 4-Br-C6H4, 4-Me-C6H4 and 4-MeO-C6H4) (5) with primary amines R-NH2 (R = Bu, 2-(1-cyclehexenil)ethyl, 2-(4- morpholinyl)ethyl, 2-phenethyl-ethyl, 2-(4-chlorophenethyl)ethyl and 2-(4- methoxyphenethyl)ethyl) (8-13), in a solvent free sealed system to give the expected products with yields between 20 to 98%. In addition, a series of new 6-substituted 4-trifluoromethyl-2H-pyran-2- ones (20) was obtained in 88 to 100% yeld, from the autocondensation reaction of 5-aryl-3-trifluoromethyl-5-methoxy-penta-2,4-dienenitriles (Ar = Ph, 4-F-C6H4, 4-Br-C6H4, 4-Me-C6H4 and 4-MeO-C6H4) (5), in a reflux system using water as solvent in the presence of HCl and 1 equivalent of ZnBr2. The pyridinimines, pyranones and dienes obtained in this work were identified and characterized by Hydrogen Nuclear Magnetic Resonance (H1NMR), Carbon-13 Nuclear Magnetic Resonance (C13 NMR), Mass Spectroscopy (GC-MS-EI), High Resolution Mass Spectroscopy (HRMS-ESI) and Elemental Analysis.